Learning-by-doing and the development of industrial districts - Antoine Soubeyran; Jacques-François Thisse (Fondazione Eni Enrico Mattei (FEEM), 1998)
Marshallian districts are locales that accommodate a large number of small firms producing similar goods to be exported and benefit from the accumulation of know-how associated with workers residing there. We study the making of such districts by assuming that the cost function of a firm is a decreasing function of the total output produced in the past by the firms established in the locale. The dynamics is described by a sequence of temporary equilibria in which firms equalise profits between locales at each period. Hence changing the spatial distribution of firms affects the production history of each district. When new firms set up in a locale, they exacerbate competition on the corresponding labour market, thus leading to a wage rise that reduces the incentives for firms to locate in the most efficient district. The short-run equilibrium distribution of firms is studied as well as the long-run properties of the adjustment process.
Keywords: O14; R12; 330; Industrial district; Learning-by-doing; Economic geography; Industriegebiet; Lernprozess; Theorie der Unternehmung; Theorie